Viability of centrosema pubescens, macropthilium artopurpureum, and clitoria ternatea seeds with soaking treatment - Sawen, Diana; Mulyadi, Mulyadi; Rumbewas, Yosina E.S. (Fakultas Peternakan Universitas Papua, 2025)
The cultivation and utilization of legumes as forage crops are often constrained by hard seed coats that inhibit germination. Physical scarification through hot-water soaking offers a practical and effective solution for farmers. This study aimed to evaluate the germination viability of Centrosema pubescens, Macroptilium atropurpureum, and Clitoria ternatea seeds following soaking treatments. The experiment was conducted over two months at the Agrostology Laboratory, Faculty of Animal Science, University of Papua, using a completely randomized factorial design with two factors: soaking temperature (60°C, 70°C, and 80°C) and legume seed type, each replicated four times. The results showed that soaking seeds at 80°C significantly improved germination time, number of germinated seeds, seedling height, number of leaves, and overall germination percentage. The shortest germination time was two days, with 2–3 seeds germinating per species. Average seedling height reached 17.96 cm, and the highest number of leaves was 10 per species. Macroptilium atropurpureum achieved the highest germination rate at 83.33%. These findings demonstrate that hot-water soaking at 80°C is an effective method to enhance seed viability in these leguminous forage species.